Solid shaft design using computer aided analysis / Mohd Nazir Ramli and Mohd Nafzanee Mohd Adnan - Ramli, Mohd Nazir; Mohd Adnan, Mohd Nafzanee (2001)
Nowadays, computer analysis has become the important process towards globalization of technology especially in engineering application. One of the important parts in using computer analysis is engineering design process, which is required to produce very precise product. This project describes the shaft design process, which usually occur in any designed product or construction using Visual C++ programming. Shear, bending moment, and torsional moment will be considered in the analysis to determine the required diameter or optimum diameter would be determined that depends on the material and the loading required. Factor of safety is also considered in the analysis. The project will produce a fully computerized product seems like a programmed model or software that could be use by users to design shaft using any materials and one type of loading which is the concentrated load. This software can be upgraded and maximize its functions by program more type of material and loading. The value of the software is demonstrated through two case studies.